Propofol for Induction and Maintenance of Anesthesia in Patients With Brugada Syndrome: A Single-Center, 25-Year, Retrospective Cohort Analysis. (June 2021) - Flamée, Panagiotis; Viaene, Kea; Tosi, Maurizio; Nogueira Carvalho, Hugo; de Asmundis, Carlo; Forget, Patrice; Poelaert, Jan
Abstract : BACKGROUND: Propofol administration in patients with Brugada syndrome (BrS) is still a matter of debate. Despite lacking evidence for its feared arrhythmogenicity, up to date, expert cardiologists recommend avoiding propofol. The main aim of this study is to assess the occurrence of malignant arrhythmias or defibrillations in patients with BrS, during and 30 days after propofol administration. The secondary aim is to investigate the occurrence of adverse events during propofol administration and hospitalization, as the 30-day readmission and 30-day mortality rate. METHODS: We performed a retrospective cohort study on patients with BrS who received propofol anytime from January 1, 1996 to September 30, 2020. Anesthesia was induced by propofol in both groups. In the total intravenous anesthesia (TIVA) group, anesthesia was maintained by propofol, while in the BOLUS group, volatile anesthesia was provided. The individual anesthetic charts and the full electronic medical records up to 30 postprocedural days were scrutinized. RESULTS: One hundred thirty-five BrS patients who underwent a total of 304 procedures were analyzed. The TIVA group included 27 patients for 33 procedures, and the BOLUS group included 108 patients for 271 procedures. In the TIVA group, the median time of propofol infusion was 60 minutes (interquartile range [IQR] = 30–180). The estimated plasma or effect-site concentration ranged between 1.0 and 6.0 µg·mL − 1 for target-controlled infusion (TCI). The infusion rate for manually driven TIVA varied between 0.8 and 10.0 mg·kg − 1 ·h − 1 . In the BOLUS group, the mean propofol dose per kilogram total body weight was 2.4 ± 0.9 mg·kg − 1 . No malignant arrhythmias or defibrillations were registered in both groups. The estimated 95% confidence interval (CI) of the risk for malignant arrhythmias in the BOLUS and TIVA groups was 0-0.011 and 0-0.091, respectively. CONCLUSIONS: The analysis of 304 anesthetic procedures in BrS patients, who received propofol, either as a TIVA or as a bolus during induction of volatile-based anesthesia, revealed no evidence of malignant arrhythmias or defibrillations. The present data do not support an increased risk with propofol-based TIVA compared to propofol-induced volatile anesthesia. Prospective studies are needed to investigate the electrophysiologic effects of propofol in BrS patents.